(3JCKjQ GdeRjL GdJQhjLj Ydi GdNOeGJ GdUMjI s - (3SYO YHGS Ydj(B, (3HMGQs ((3GdEScfOQjI (B:s (3OGQ GdJYdje GdLGeYj(B,s, 2020)
(3JfGhd gPG GdcJGH ehVhY JCKjQ GdeRjL GdJShjbj Ydi GdNOeGJ GdUMjI MjK SYJ gPg GdOQGSI Gdi GYWGA UhQI TGedI Yf gPjf GdeJZjQjf (B.(3HGdGVGaI Gdi JUeje eNWW aQVj jhVM WHjYI GdYdGbI Hjf YfGUQ GdeRjL GdJQhjLj hGdNOeI GdUMjI (B. s
(3GdHjHdjhZQGajG U(B.221s
Keywords: (3GdJQhjLs; (3GdNOeGJ GdUMjIs